Unusual fluorescence of: O-phenylazonaphthol derivatives with aggregation-induced emission and their use in two-photon cell imaging - Yoon, Yeoju; Jo, Seonyoung; Park, Sang Jun; Kim, Hwan Myung; Kim, Dongwook; Lee, Taek Seung (Chemical Communications, 2019)
o-Phenylazonaphthol (o-PAN) derivatives including 6-bromo-1-((4-bromophenyl)diazenyl)naphthalen-2-ol (AN-Br-OH) and 1-phenylazo-2-naphthol (AN-OH, known as Sudan I (Color Index 12055)) were synthesized to investigate their fluorogenic behaviors, in which their aggregated-induced emission (AIE) is reported. The o-PANs showed a two-photon absorption. The protection of hydroxyl groups in o-PANs was used for fluorescence imaging of esterase-expressed HepG2 cells, which is potentially suitable for sensing and two-photon cell imaging applications.
Keywords: Esterases; Fluorescent Dyes; Hep G2 Cells; Humans; Limit of Detection; Microscopy, Fluorescence, Multiphoton; Naphthols; Spectrometry, Fluorescence; Ultraviolet Rays